Analysis of input impedance influence on calibration of charge conditioning amplifiers. (December 2021) - Ripper, Gustavo P.; Dias, Ronaldo S.; Micheli, Giancarlo B.; Ferreira, Cauê D.
Abstract: This paper presents the updates implemented by the Vibration Laboratory of INMETRO on the electrical calibration of charge conditioning amplifiers. We can now carry out both standard classical calibrations with fixed in-series capacitors and including an adjustable parallel capacitance to match the total capacitance of a given pair of accelerometer plus cable. The calibration system and some analysis of measurement results are presented.